The Protective Effect of Different Polar Solvent Extracts of Er Miao San on Rats with Adjuvant Arthritis. (20th February 2020) - Zhang, Wei; Zhang, Qiying; Xuan, Zihua; Liang, Juan; Yang, Dongping; Ding, Meihuizi; Zhu, Housheng; Su, Bo; Dai, Xing; Jia, Xiaoyi
Abstract : Objective . The aim of this study was to evaluate the antiarthritic effects of different polar solvent extracts of Er Miao San (EMS) on model rats with adjuvant arthritis (AA) and screen the effective pats of EMS in the treatment of arthritis. Methods . Four different polar solvent extracts of EMS such as petroleum ether (PE), methylene chloride (CH2 Cl2 ), ethyl acetate (EtOAc), and n -butanol ( n -BuOH) were extracted and separated by different solvent polar extraction. Different polar parts of the aqueous extract of EMS were orally administered for 14 days to AA rats. Progression of clinical signs such as edema of paws and polyarthritis index was measured. The ankle joint changes were observed by pathological sections. ELISA was used to measure cytokines in the serum according to the manufacturer's instructions. UHPLC measured the effective parts of EMS. Results . Administration of EtOAc and CH2 Cl2 parts remarkably inhibited the paw swelling, decreased the index of arthritis, decreased the body weight loss, and improved the changes of histopathology. Furthermore, the concentrations of proinflammatory cytokines (TNF- α, IL-1 β, and IL-6) were significantly lower, while the anti-inflammatory cytokine (IL-10) was remarkably higher compared with that in the model group. And the result of UHPLC analysis indicated that the effective parts of EMS contain berberine and atractylodin. Conclusions . EtOAc and CH2 Cl2 are the effective parts of EMS that can improve arthritis. In particular, berberine and atractylodin may be responsible for the antiarthritic activity of EMS. This research provided pharmacological and chemical foundation for the application of EMS in treating rheumatoid arthritis (RA).